Case report: a rare case of duodenal metastasis of endometrial carcinosarcoma - Xiao, Lin; Sun, Lie (Frontiers in Oncology, 2024)
Endometrial carcinosarcoma is a tumor characterized by the coexistence of carcinoma and sarcoma. It almost only occurs in postmenopausal women, and the average five-year survival rate is less than 30%. Endometrial carcinosarcoma is very aggressive and usually has high tumor recurrence and mortality rates. Endometrial carcinosarcoma often metastasizes to the lymph nodes, lungs and peritoneum. Here, we report a rare case of duodenal metastasis of endometrial carcinosarcoma.